Brahms's Elegies the Poetics of Loss in Nineteenth-Century German Culture - Grimes, Nicole ca. 20./21. Jh (Music in Context, 2021)
Nicole Grimes provides a compellingly fresh perspective on a series of Brahms's elegiac works by bringing together the disciplines of historical musicology, German studies, and cultural history. Her exploration of the expressive potential of Schicksalslied, Nänie, Gesang der Parzen, and the Vier ernste Gesänge reveals the philosophical weight of this music. She considers the German tradition of the poetics of loss that extends from the late-eighteenth-century texts by Hölderlin, Schiller and Goethe set by Brahms, and includes other philosophical and poetic works present in his library, to the mid-twentieth-century aesthetics of Adorno, who was preoccupied as much by Brahms as by their shared literary heritage. Her multifaceted focus on endings - the end of tonality, the end of the nineteenth century, and themes of loss in the music - illuminates our understanding of Brahms and lateness, and the place of Brahms in the fabric of modernist culture